Enhanced Levels of Peroxisome-Derived H2O2 Do Not Induce Pexophagy but Impair Autophagic Flux in HEK-293 and HeLa Cells - Hongli Li; Celien Lismont; Cláudio F. Costa; Mohamed A. F. Hussein; Myriam Baes; Marc Fransen (MDPI AG, 2023)
Peroxisomes are functionally specialized organelles that harbor multiple hydrogen peroxide (H2O2)-producing and -degrading enzymes. Given that this oxidant functions as a major redox signaling agent, peroxisomes have the intrinsic ability to mediate and modulate H2O2-driven processes, including autophagy. However, it remains unclear whether changes in peroxisomal H2O2 (po-H2O2) emission impact the autophagic process and to which extent peroxisomes with a disturbed H2O2 metabolism are selectively eliminated through a process called "pexophagy". To address these issues, we generated and validated HEK-293 and HeLa pexophagy reporter cell lines in which the production of po-H2O2 can be modulated. We demonstrate that (i) po-H2O2 can oxidatively modify multiple selective autophagy receptors and core autophagy proteins, (ii) neither modest nor robust levels of po-H2O2 emission act as a prime determinant of pexophagy, and (iii) high levels of po-H2O2 impair autophagic flux by oxidative inhibition of enzymes involved in LC3II formation. Unexpectedly, our analyses also revealed that the autophagy receptor optineurin can be recruited to peroxisomes, thereby triggering pexophagy. In summary, these findings lend support to the idea that, during cellular and organismal aging, peroxisomes with enhanced H2O2 release can escape pexophagy and downregulate autophagic activity, thereby perpetuating the accumulation of damaged and toxic cellular debris.